Image guided brachytherapy in locally advanced cervical cancer: Improved pelvic control and survival in RetroEMBRACE, a multicenter cohort study - Alina Sturdza (2018)
© 2016 Purpose Image guided brachytherapy (IGBT) for locally advanced cervical cancer allows dose escalation to the high-risk clinical target volume (HRCTV) while sparing organs at risk (OAR). This is the first comprehensive report on clinical outcome in a large multi-institutional cohort. Patients and methods From twelve centres 731 patients, treated with definitive EBRT ± concurrent chemotherapy followed by IGBT, were analysed. Kaplan–Meier estimates at 3/5 years were calculated for local control (LC, primary endpoint), pelvic control (PC), overall survival (OS), cancer specific survival (CSS). In 610 patients, G3–4 late toxicity (CTCAEv3.0) was reported. Results Median follow up was 43 months, percent of patients per FIGO stage IA/IB/IIA 22.8%, IIB 50.4%, IIIA–IVB 26.8%. 84.8% had squamous cell carcinomas; 40.5% lymph node involvement. Mean EBRT dose was 46 ± 2.5 Gy; 77.4% received concurrent chemotherapy. Mean D90 HRCTV was 87 ± 15 Gy (EQD210), mean D2cc was: bladder 81 ± 22 Gy, rectum 64 ± 9 Gy, sigmoid 66 ± 10 Gy and bowel 64 ± 9 Gy (all EQD23). The 3/5-year actuarial LC, PC, CSS, OS were 91%/89%, 87%/84%, 79%/73%, 74%/65%. Actuarial LC at 3/5 years for IB, IIB, IIIB was 98%/98%, 93%/91%, 79%/75%. Actuarial PC at 3/5 years for IB, IIB, IIIB was 96%/96%, 89%/87%, 73%/67%. Actuarial 5-year G3–G5 morbidity was 5%, 7%, 5% for bladder, gastrointestinal tract, vagina. Conclusion IGBT combined with radio-chemotherapy leads to excellent LC (91%), PC (87%), OS (74%), CSS (79%) with limited severe morbidity.